(untitled) - Baglet, Desmond (Oxford, 1997)
Malcolm Jaggard is a spycatcher, and a servant of the politicians. He's hard, and togh, and intelligent - and he wants to marry Penny Ashton, a scientist, and the daughter of the scientist George Ashton. Then the Ashtons' comfortable world is suddenly shattered, and Malcolm is ordered by his politicians bosses to protect Ashton. Malcolm needs more knowledge, and he can't get it. So he fights for it. But knowledge is power, and servants must not have power. As his search for Ashton turns into a desperate and violent manhunt, Malcolm finds knowledge. But he also finds himself in the long-running war between scientists and politicians - a war that it is safer to keep out of, a war where. "We have met the enemy, and he is us"
Keywords: English fiction,English literature; 20th century